The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13756-015-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage of methicillin resistant Staphylococcus aureus among health care workers at a tertiary care hospital in Western Nepal

Abstract: BackgroundStaphylococcus aureus is a frequent cause of infections in both the community and hospital. Methicillin-resistant Staphylococcus aureus continues to be an important nosocomial pathogen and infections are often difficult to manage due to its resistance to multiple antibiotics. Healthcare workers are important source of nosocomial transmission of MRSA. This study aimed to determine the nasal carriage rate of S. aureus and MRSA among healthcare workers at Universal College of Medical Sciences and Teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
54
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 18 publications
15
54
9
2
Order By: Relevance
“…[16][17][18] In our study, the overall rate of nasal carriage of MRSA was found to be 7.5%, which was in accordance with the finding by Malini et al (8%). 19 However, higher rates of MRSA carriage among HCWs were reported by Pant et al 3 (54%), 3 4 Health care workers are the sources of MRSA, who are responsible for transferring of this pathogen to the patients, 3 and the haphazard use of the antibiotics may have contributed to the emergence of the MRSA. Further, the local prevalence of MRSA may have attributed to the difference in carriage rates reported by different authors.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…[16][17][18] In our study, the overall rate of nasal carriage of MRSA was found to be 7.5%, which was in accordance with the finding by Malini et al (8%). 19 However, higher rates of MRSA carriage among HCWs were reported by Pant et al 3 (54%), 3 4 Health care workers are the sources of MRSA, who are responsible for transferring of this pathogen to the patients, 3 and the haphazard use of the antibiotics may have contributed to the emergence of the MRSA. Further, the local prevalence of MRSA may have attributed to the difference in carriage rates reported by different authors.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, the higher percentage of lab personnel (10.5%) were MRSA carriers followed by nurses (9.9%) and doctors(6.4%).But in a study by Khanal et al,higher percentage of doctors (20.8%) were S. aureus carriers and higher percentage of nurses (7.8%) were MRSA carriers. 4 Similarly, Shibabaw et al reported the MRSA carriage percentage to be highest among nurses (21.2%), followed by doctors (12.5%) and laboratory technicians (12.5%) and S. aureus carriage percentage to be highest among doctors (37.5%) followed by nurses (34.6%) and laboratory technicians (25%). 20 The highest percentages of S. aureus and MRSA carriage found among laboratory personnel in our study might be due to the contact of the laboratory personnel to the infected samples received from different wards.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations